Peran Pola Asuh Permisif, Iklim Sekolah, dan Motivasi Berprestasi Terhadap Perilaku Membolos Siswa - Muin, Salwa (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
This research aims to the role of permissive parenting, school atmosphere, and achievement motivation towards studentsâ truant behavior. This is a correlational research. The quantitative approch is used in this research. The participants were 200 students of SMK PIRI 1 Yogyakarta. There was a form of scale of truant behavior, permissive parenting, school atmosphere and achivement motivation that used as the instrument of this research. The data were analyzed using multiple regression analysis. Based on the analysis results, the obtained data showed a coefficient of 22.044 with the sig. 0,000. The results of the study showed that there is a significant influence between permissive parenting towards studentsâ truant behavior , school atmosphere and achievement motivation by 25,2%. Specifically, there is a significant influence between permissive parenting towards studentsâ truant behavior by 18,3%, there is no significant influence between school atmosphere towards studentsâ truant behavior by 1,6%, there is a significant influence between achievement motivation towards studentsâ truant behavior by 24,5%. This research findings can be considered as useful information for the parents in order to provide an effective parenting for their children. On the other hand, these findings can be used as the ponder in developing guidance and counseling services to reduce studentsâ truant behavior.